Creating a strategic energy reduction plan - Offerman, Scott, 1966- (The Fairmont Press, Inc. : Taylor & Francis Ltd., 2014)
"This book provides a simple, easily followed process for auditing building operations in order to identify and reduce energy consumption. The crucial steps of this process involve assessing the facility's current conditions, understanding and analyzing the operational and cost-based opportunities, reporting the findings, and then documenting the plan. The book discusses the full scope of building components and systems, including how each impacts energy efficiency, and then goes on to describe the operational energy efficiencies that can be gained by implementing no-cost changes or alternative maintenance activities already funded. Capital improvement opportunities, along with evaluating return on investment and life cycle replacement of equipment are also covered. The four step process described in this book will serve as a valuable tool for every building operator seeking to improve facility energy performance."--Amazon.com viewed July 23, 2020
Includes index.
Keywords: Buildings -- Energy conservation -- Handbooks, manuals, etc.; Energy auditing -- Handbooks, manuals, etc.; elektronické knihy; electronic books